Bandgap Funneling in Bismuth‐Based Hybrid Perovskite Photocatalyst with Efficient Visible‐Light‐Driven Hydrogen Evolution (Small Methods 8/2022). Issue 8 (17th August 2022) - Tang, Yunqi; Mak, Chun Hong; Wang, Chen; Fu, Yu; Li, Fang‐Fang; Jia, Guohua; Hsieh, Chang‐Wei; Shen, Hsin‐Hui; Colmenares, Juan Carlos; Song, Haisheng; Yuan, Mingjian; Chen, Yue; et al.
Abstract : Back Cover In article number 2200326, Chen, Hsu, and co‐workers developed a novel, environmentally friendly mixed halide perovskites MA3 Bi2 Cl9 –xIx with a bandgap funnel structure. Bandgap funneling of lead‐free bismuth‐based MA3 Bi2 Cl9 –xIx photocatalysts provides an "energy staircase" for electrons and holes, resulting in enhanced charge‐carrier separation and efficient photocatalytic redox reaction.